Partial Least Square (PLS) Analysis: The Relationship of Production Management and Business Analysis of Goat Farm in Deli Tua Village, Namorambe District, North Sumatera, Indonesia - Mudhita Zikkrullah Ritonga; Risdawati Br Ginting (Talenta Publisher, 2019)
Goat farm business provides income both for farmers and the community. Goat farming is very potential because the goats have adult sex and adult body and the length of goat breeding is very short compared to other ruminants. The existence of goat livestock business can create jobs and business that it can help the people’s economy. This study aims to identify the relationship between production management and business analysis of goat farm in Deli Tua Village, Namorambe District, North Sumatera, Indonesia. This study used data from nine respondents who own 25-50 goats that were determined by purposive sampling. The data were analyzed by using Partial Least Square (PLS) method shows a significant relationship between production management and business analysis. Keeping management is production management is a indicators of production management which gives a very influential effect on business analysis